Presentation, imaging and treatment of common musculoskeletal conditions : MRI-arthroscopy correlation - Miller, Mark D.; Sanders, Timothy G.; ClinicalKey eBooks (Philadelphia, Pa. : Elsevier, 2012)
Take the mystery out of MRI interpretation and its relationship to arthroscopy with this book by Drs. Mark D. Miller and Timothy G. Sanders. Abundantly illustrated with MR, arthroscopic, and anatomical images, this new title offers both orthopaedists and radiologists a correlated, systematic approach to diagnosis, helping you achieve accurate evaluations and ensuring that all clinically relevant structures are adequately assessed. An accompanying case-based DVD illustrates pathology and repair, with side-by-side comparisons of MRI and arthroscopic findings in the same patient. Improve diagnostic accuracy, surgical planning/decision making, and patient outcomes by seeing how to correlate MRI and arthroscopic findings. Gain an enhanced appreciation of the sensitivity and specificity of MRI as a tool in musculoskeletal diagnosis. Enhance your diagnostic skills by reviewing illustrative case studies for each major joint, examining specific MRI and arthroscopic findings and considering the range of possible diagnoses. View side-by-side comparisons of MRI and arthroscopic footage in the same patient - augmented by line illustrations that orient the arthroscopic views - by watching the videos on the bound-in DVD. Take the mystery out of MRI interpretation to assess more confidently.
pt. 1. Introduction -- pt. 2. Shoulder -- pt. 3. Elbow -- pt. 4. Wrist and hand -- pt. 5. Hip -- pt. 6. Knee -- pt. 7. Leg.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Magnetic resonance imaging; Arthroscopy; Musculoskeletal system -- Wounds and injuries; Musculoskeletal system -- Diseases; Musculoskeletal Diseases -- diagnosis; Musculoskeletal Diseases -- therapy; Arthroscopy -- methods; Magnetic Resonance Imaging -- methods; Musculoskeletal System -- injuries; Musculoskeletal System -- diagnostic imaging; Appareil locomoteur -- Imagerie; Appareil locomoteur -- Maladies -- Traitement; Appareil locomoteur -- Maladies -- Atlas; HEALTH & FITNESS -- Diseases -- Musculoskeletal; MEDICAL -- Orthopedics; MEDICAL -- Rheumatology; Arthroscopy; Magnetic resonance imaging; Musculoskeletal system -- Diseases; Musculoskeletal system -- Wounds and injuries; Electronic books